The acquisition of survey knowledge for local and global landmark configurations under time pressure. Issue 3 (3rd July 2019) - Credé, Sascha; Thrash, Tyler; Hölscher, Christoph; Fabrikant, Sara Irina
ABSTRACT: The influence of stress states on cognition is widely recognized. However, the manner in which stress affects survey knowledge acquisition is still unresolved. For the present study, we investigated whether survey knowledge acquisition during a stressful task (i.e., under time pressure) is more accurate for the mental representation of global or local landmarks. Participants navigated through virtual cities with a navigation aid and explicit learning instructions for different landmark configurations. Participants' judgments of relative direction (JRDs) suggest that global landmark configurations were not represented more accurately than local landmark configurations and that survey knowledge acquisition was not impaired under time pressure. In contrast to prior findings, our results indicate the limitations of the utility of global landmarks for spatial knowledge acquisition.